Biallelic loss‐of‐function variants in EXOC6B are associated with impaired primary ciliogenesis and cause spondylo‐epi‐metaphyseal dysplasia with joint laxity type 3. Issue 12 (8th October 2022) - Simsek‐Kiper, Pelin Ozlem; Jacob, Prince; Upadhyai, Priyanka; Taşkıran, Zihni Ekim; Guleria, Vishal S.; Karaosmanoglu, Beren; Imren, Gozde; Gocmen, Rahsan; Bhavani, Gandham S.; Kausthubham, Neethukrishna; Shah, Hitesh; Utine, Gulen Eda; et al.
Abstract: Spondylo‐epi‐metaphyseal dysplasias with joint laxity, type 3 (SEMDJL3) is a genetic skeletal disorder characterized by multiple joint dislocations, caused by biallelic pathogenic variants in the EXOC6B gene. Only four individuals from two families have been reported to have this condition to date. The molecular pathogenesis related to primary ciliogenesis has not been enumerated in subjects with SEMDJL3. In this study, we report two additional affected individuals from unrelated families with biallelic pathogenic variants, c.2122+15447_2197‐59588del and c.401T>G in EXOC6B identified by exome sequencing. One of the affected individuals had an intellectual disability and central nervous system anomalies, including hydrocephalus, hypoplastic mesencephalon, and thin corpus callosum. Using the fibroblast cell lines, we demonstrate the primary evidence for the abrogation of exocytosis in an individual with SEMDLJ3 leading to impaired primary ciliogenesis. Osteogenesis differentiation and pathways related to the extracellular matrix were also found to be reduced. Additionally, we provide a review of the clinical and molecular profile of all the mutation‐proven patients reported hitherto, thereby further characterizing SEMDJL3. SEMDJL3 with biallelic pathogenic variants in EXOC6B might represent yet another ciliopathy with central nervous system involvement and joint dislocations.